A Canonical Correlation Analysis of Commercial Bank Asset/Liability Structures - Simonson, Donald G.; Stowe, John D.; Watson, Collin J. (Journal of Financial and Quantitative Analysis, 1983)
Commercial banks have been the subjects of a large body of empirical research employing regression and econometric models and discriminant analysis. The purpose of this paper is to empirically identify and describe relationships, including hedging behavior, between the asset side and the liability/capital side of the balance sheets of a cross-section of large U.S. banks. Canonical correlation analysis is the statistical technique that is employed. Unlike regression analysis which explains the behavior of a single dependent variable as a function of a set of independent variables, canonical correlation analysis relates two sets of variables. In the present case, one set of variables is the composition of the lefthand side of the balance sheet and the other set is the right-hand side. The variables used in this study are asset and liability/capital categories expressed as a proportion of total bank assets (i.e., a percentage breakdown of the balance sheet or a common size statement). These proportions are used in lieu of the more usual financial ratios and no information exogenous to the bank is employed.